2020
DOI: 10.2169/internalmedicine.5014-20
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease-19 Pneumonia with Facial Nerve Palsy and Olfactory Disturbance

Abstract: The novel coronavirus disease-2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2, has spread worldwide from China. There are no case reports from Asia of COVID-19 with facial paralysis and olfactory disturbance. We herein report a case of COVID-19 pneumonia in a Japanese woman who showed facial nerve palsy and olfactory disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 9 publications
0
38
1
2
Order By: Relevance
“…4 Homma et al described a patient with ARI symptoms, olfactory disturbance, and mild facial nerve palsy, though the exact temporal sequence was not described. 5 To our knowledge, these two cases are the only two in literature with isolated facial nerve involvement without other neurological deficits nor ARI symptoms. Further cases would be helpful to elucidate the exact pathogenesis of facial nerve palsy in COVID-19.…”
Section: Case Reportsmentioning
confidence: 67%
“…4 Homma et al described a patient with ARI symptoms, olfactory disturbance, and mild facial nerve palsy, though the exact temporal sequence was not described. 5 To our knowledge, these two cases are the only two in literature with isolated facial nerve involvement without other neurological deficits nor ARI symptoms. Further cases would be helpful to elucidate the exact pathogenesis of facial nerve palsy in COVID-19.…”
Section: Case Reportsmentioning
confidence: 67%
“…The second case had lower limbs’ weakness along with foot drop, areflexia, polyneuropathy, and gastroplegia. Case report France Arnaud et al, 2020 [ 65 ] Cranial nerve involvement, paresthesia of the hands and feet, progressive lower limb weakness, dysphagia, and areflexic quadriplegia Case report Spain Esteban Molina et al, 2020 [ 66 ] Dysphagia, paresthesia, tetraplegia, areflexia, limb weakness, radiating pain, and inflammatory polyradiculoneuropathy Case report Spain Marta-Enguita et al, 2020 [ 67 ] GBS in association with leptomeningeal enhancement Case report Spain Sancho-Saldaña et al, 2020 [ 68 ] Dysphagia, quadriparesis, quadriplegia, global areflexia, and bilateral facial palsy Case report Spain Velayos Galán et al 2020 [ 69 ] Progressive limb weakness and foot dysaesthesia, myalgias, paresis, and global areflexia Case report UK Webb et al, 2020 [ 70 ] One of 841 patients Retrospective Spain Romero-Sanchez et al, 2020 [ 71 ••] Myositis Proximal lower limb muscle weakness, causing to fall Case report France Beydon et al, 2020 [ 91 ] Severe proximal and bulbar weakness Case report USA Zhang et al, 2020 [ 92 ] Cranial polyneuropathy Facial nerve palsy and olfactory disturbance Case report Japan Homma et al, 2020 [ 96 ] Ipsilateral fifth and seventh cranial nerve involvement Case report USA Gogia et al, 2020 [ 97 ] Neuromuscular junction disorders MG in 3 cases Case report Italy Restivo et al, 2020 [ …”
Section: Guillain-barré Syndrome Spectrumsmentioning
confidence: 99%
“…Recent evidence indicates that COVID-19 may also lead to multiple cranial neuropathies, as well as the more recognized high incidence of anosmia with infection, with rates of up to 73% of those infected [ 95 ]. A 35-year-old COVID-19 patient had the right facial paralysis and olfactory disturbances [ 96 ] and an almost complete loss of sense of taste on the right side of her tongue, with only the preservation of a sense of sweetness. Her sense of smell was also completely absent as she could not smell shampoo, coffee, or soy sauce.…”
Section: Multiple Cranial Neuropathiesmentioning
confidence: 99%
“…Among the 68 studies on the CNS effects, 46 were case reports [16,17,, followed by 10 retrospective studies [64][65][66][67][68][69][70][71][72][73], 4 observational cohort studies [74][75][76][77], 3 prospective studies [78][79][80], 3 case-control studies [81][82][83] and 2 cross-sectional studies [84,85]. Among the 21 studies regarding PNS disorders, there were 19 case reports [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104], 1 prospective study [78] and 1 retrospective study [68]. Two studies reported both CNS and PNS effects of COVID-19 [68,78].…”
Section: Categorization and Characteristics Of The Selected Studiesmentioning
confidence: 99%
“…Homma and colleagues [92] reported the case of a 35-year-old patient who developed facial nerve palsy secondary to COVID-19. She had no pre-existing pathologies but she was a usual smoker.…”
Section: Effects Of Sars-cov-2 On Pnsmentioning
confidence: 99%